Sporormiella and the late Holocene extinctions in Madagascar - Burney, David A. (National Academy of Sciences, 2003)
Fossil spores of the dung fungus Sporormiella spp. in sediment cores from throughout Madagascar provide new information concerning megafaunal extinction and the introduction of livestock. Sporormiella percentages are very high in prehuman southwest Madagascar, but at the site with best stratigraphic resolution the spore declines sharply by ≈1,720 yr B.P. (radiocarbon years ago). Within a few centuries there is a concomitant rise in microscopic charcoal that probably represents human transformation of the local environment. Reduced megaherbivore biomass in wooded savannas may have resulted in increased plant biomass and more severe fires. Some now-extinct taxa persisted locally for a millennium or more after the inferred megafaunal decline. Sites in closed humid forests of northwest Madagascar and a montane ericoid formation of the central highlands show only low to moderate Sporormiella percentages before humans. A subsequent rise in spore concentrations, thought to be evidence for livestock proliferation, occurs earliest at Amparihibe in the northwest at ≈1,130 yr B.P.